Fake News sobre a Covid-19 nas aulas de Química: uma abordagem didática na Monitoria das Práticas de Ensino - CAPISTRANO, Francisco Frank Dourado (2022)
This Course Completion Work is configured as recommended by Normative Instruction No. 01/2022 of the Dean of Graduation of the Federal University of Pará, which provided for the regulation of TCC activities, made more flexible due to the consequences arising from the COVID-19 pandemic. Thus, the Expanded Abstract submitted to the SEPEDUC event will be used as a requirement for analysis by the review board of this text. Such written production is based on the proliferation of fake news about Covid-19. The present academic construction is an experience report carried out in the Monitoring of Teaching Practices with Graduating Students in Chemistry at UFPA, which intended to present productions and analyzes of fake news of a scientific nature. The work developed has a qualitative nature, based on an investigative bias about scientific fake news. As results achieved, we highlight the critical perception of undergraduates regarding elements present in fake news. The findings also highlight the relevance of the theme for undergraduates regarding the applicability of chemical-scientific knowledge and the reaffirmation of their role as a chemistry teacher in the face of fake narratives. Finally, it is defended to carry out investigations involving scientific fake news in chemistry classes aiming at the establishment of a more critical, applicable and problematizing teaching.